Exploring Vocabulary Learning Strategies in EFL: A Case Study of Sudanese University Students - Amel Zulfukar Hassan Adlan; Eko Risdianto (CV Media Inti Teknologi, 2026)
Background: Sudanese University students face significant challenges in English proficiency due to historical Arabicization policies and outdated pedagogical frameworks. While vocabulary is a primary predictor of linguistic success, a systemic gap exists between strategy awareness and long-term lexical retention. Aims: This study investigated the relationship between Vocabulary Learning Strategies (VLS), institutional support, and actual proficiency (receptive and productive) among Sudanese undergraduates. Methods: Using s triangulated quantitative and documentary design (N=240), the study utilized the Vocabulary Levels Test (VLT), Lex30, a Likert-scale VLS questionnaire, and a systematic analysis of university syllabi. Data were analyzed using Structural Equation Modelling (SEM) and psychometric validation. Results: Psychometric tools demonstrated strong internal validity (VLT α = 0.86; Lex30 M = 14.2/30). Latent profile analysis revealed a severe